Reconstructing bodies : biomedicine, health, and nation-building in South Korea since 1945 - DiMoia, John Paul, 1966- (Studies of the Weatherhead East Asian Institute, Columbia University., 2013)
"South Korea represents one of the world's most enthusiastic markets for plastic surgery. The growth of this market is particularly fascinating as access to medical care and surgery arose only recently with economic growth since the 1980s. Reconstructing Bodies traces the development of a medical infrastructure in the Republic of Korea (ROK) from 1945 to the present, arguing that the plastic surgery craze and the related development of biotech ambitions is deeply rooted in historical experience. Tracking the ROK's transition and independence from Japan, John P. DiMoia explains how the South Korean government mobilized biomedical resources and technologies to consolidate its desired image of a modern and progressive nation. Offering in-depth accounts of illustrative transformations, DiMoia narrates South Korean biomedical practice, including Seoul National University Hospital's emergence as an international biomedical site, state-directed family planning and anti-parasite campaigns, and the emerging market for aesthetic and plastic surgery, reflecting how South Koreans have appropriated medicine and surgery for themselves as individuals, increasingly prioritizing private forms of health care"--Provided by publisher.